2002
DOI: 10.1161/hc0502.102964
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Changes in Three-Dimensional Architecture and Vascular Volume of Transmural Coronary Microvasculature Between Diastolic- and Systolic-Arrested Rat Hearts

Abstract: Background-The phase difference of coronary arterial and venous flows indicates the importance of intramyocardial capacitance vessels in storing diastolic flow and in discharging volume in systole. However, the anatomic and functional characteristics of the capacitance vessels are unclear. We aimed to clarify those characteristics with their transmural difference by 3D visualization of transmural microvessels under diastole and systole. Methods and Results-We performed complete intracoronary filling of a contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
100
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 108 publications
(107 citation statements)
references
References 28 publications
7
100
0
Order By: Relevance
“…The large variability in myocardial flow per 100 g tissue that is found indicates variation in anatomical characteristics of the coronary arterial tree [7,16]. Recent studies visualized the anatomical structure of the coronary arterial tree in the intact heart [10,14]. Rodriguez-Porcel et al [10] found that myocardial architecture was altered in experimental hypercholesterolemia; hypercholesterolemia increased sub-endocardial microvascular density and sprouting.…”
Section: Introductionmentioning
confidence: 99%
“…The large variability in myocardial flow per 100 g tissue that is found indicates variation in anatomical characteristics of the coronary arterial tree [7,16]. Recent studies visualized the anatomical structure of the coronary arterial tree in the intact heart [10,14]. Rodriguez-Porcel et al [10] found that myocardial architecture was altered in experimental hypercholesterolemia; hypercholesterolemia increased sub-endocardial microvascular density and sprouting.…”
Section: Introductionmentioning
confidence: 99%
“…15,16 The capillary microvessels show a greater phasic change in microvascular resistance, which may function to maintain the capillary patency during systole. 17 Consequently, the increase in subendocardial resistance induced by ischemia causes a decrease in the capacitance of microvessels during systole.…”
mentioning
confidence: 99%
“…In all the computational work so far, we have considered α = β = 1 cm, so the arteriole and venule sections are each 1 cm × 1 cm in dimension, and Q = 0.025W (ml min −1 ) Similarly, we can obtain the flow rate for square ducts as Q = 0.025W (ml min −1 ) 2.3.2 Porosity-We restrict the porosity to a specified value γ. The value of γ is varied from 0.4 to 0.7 [8,25,33,36]. Porosity of the network is indicative of the percent of blood in microvasculature and, in general, can vary depending on the permeability of vasculature.…”
Section: Constraintsmentioning
confidence: 99%